Democracy of sound music piracy and the remaking of American copyright in the twentieth century - Cummings, Alex Sayf (Oxford University Press, 2013)
'Democracy of Sound' tells the story of the pirates, radicals, jazzbos, deadheads, and DJs who challenged the record industry for control of recorded sound throughout the 20th century. A political and cultural history, it shows how the primacy of 'intellectual property' gradually eclipsed an American political tradition that was suspicious of monopolies and favoured free competition.